Theaflavin alleviates inflammatory response and brain injury induced by cerebral hemorrhage via inhibiting the nuclear transcription factor kappa β-related pathway in rats - Fu G; Wang H; Cai Y; Zhao H; Fu W (Dove Medical Press, 2018)
Guanglei Fu,1 Hua Wang,2 Youli Cai,2 Hui Zhao,2 Wenjun Fu2 1Department of Neurology, The First Affiliated Hospital of Jinan University, Guangzhou, People’s Republic of China; 2School of Basic Medical Science, Guangzhou University of Chinese Medicine, Guangzhou, People’s Republic of China Objective: Intracerebral hemorrhage (ICH) is one of the most common acute cerebrovascular diseases with high mortality. Numerous studies have shown that inflammatory response played an important role in ICH-induced brain injury. Theaflavin (TF) extracted from black tea has various biological functions including anti-inflammatory activity. In this study, we investigated whether TF could inhibit ICH-induced inflammatory response in rats and explored its mechanism.Materials and methods: ICH rat models were induced with type VII collagenase and pretreated with TF by gavage in different doses (25 mg/kg–100 mg/kg). Twenty-four hours after ICH attack, we evaluated the rats’ behavioral performance, the blood–brain barrier (BBB) integrity, and the formation of cerebral edema. The levels of reactive oxygen species (ROS) and inflammatory cytokines were examined by 2',7'-dichlorofluorescin diacetate and enzyme-linked immunosorbent assay. Nissl staining and transferase dUTP nick end labeling (TUNEL) were aimed to detect the neuron loss and apoptosis, the mechanism of which was explored by Western blot.Results: It was found that in the pretreated ICH rats TF significantly alleviated the behavioral defects, protected BBB integrity, and decreased the formation of cerebral edema and the levels of ROS as well as inflammatory cytokines (including interleukin-1 beta [IL-1β], IL-18, tumor nectosis factor-alpha, interferon-γ, transforming growth factor beta, and (C-X-C motif) ligand 1 [CXCL1]). Nissl staining and TUNEL displayed TF could protect against the neuron loss and apoptosis via inhibiting the activation of nuclear transcription factor kappa-β-p65 (NF-κβ-p65), caspase-1, and IL-1β. We also found that phorbol 12-myristate 13-acetate, a nonspecific activator of NF-κβ-p65, weakened the positive effect of TF on ICH-induced neural defects and neuron apoptosis by upregulating NF-κβ-related signaling pathway.Conclusion: TF could alleviate ICH-induced inflammatory responses and brain injury in rats via inhibiting NF-κβ-related pathway, which may provide a new way for the therapy of ICH. Keywords: cerebral hemorrhage, theaflavin, inflammatory response, NF-κβ-p65